The Impact of Mitochondrial Dysfunction in Amyotrophic Lateral Sclerosis - Zhao, Jiantao; Wang, Xuemei; Huo, Zijun; Chen, Yanchun; Liu, Jinmeng; Zhao, Zhenhan; Meng, Fandi; Su, Qi; Bao, Weiwei; Zhang, Lingyun; Wen, Shuang; Wang, Xin; et al. (Cells (Basel, Switzerland), 2022)
Amyotrophic lateral sclerosis (ALS) is a rapidly progressive and highly fatal neurodegenerative disease. Although the pathogenesis of ALS remains unclear, increasing evidence suggests that a key contributing factor is mitochondrial dysfunction. Mitochondria are organelles in eukaryotic cells responsible for bioenergy production, cellular metabolism, signal transduction, calcium homeostasis, and immune responses and the stability of their function plays a crucial role in neurons. A single disorder or defect in mitochondrial function can lead to pathological changes in cells, such as an impaired calcium buffer period, excessive generation of free radicals, increased mitochondrial membrane permeability, and oxidative stress (OS). Recent research has also shown that these mitochondrial dysfunctions are also associated with pathological changes in ALS and are believed to be commonly involved in the pathogenesis of the disease. This article reviews the latest research on mitochondrial dysfunction and its impact on the progression of ALS, with specific attention to the potential of novel therapeutic strategies targeting mitochondrial dysfunction.